2018
DOI: 10.3389/fimmu.2018.02451
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking Tree and Ancestral Sequence Inference for B Cell Receptor Sequences

Abstract: B cell receptor sequences evolve during affinity maturation according to a Darwinian process of mutation and selection. Phylogenetic tools are used extensively to reconstruct ancestral sequences and phylogenetic trees from affinity-matured sequences. In addition to using general-purpose phylogenetic methods, researchers have developed new tools to accommodate the special features of B cell sequence evolution. However, the performance of classical phylogenetic techniques in the presence of B cell-specific featu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
76
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(79 citation statements)
references
References 84 publications
3
76
0
Order By: Relevance
“…Davidsen and Matsen [308] compared maximum likelihood and maximum parsimony methods for BCR lineage reconstruction. They concluded that an improved and informed maximum parsimony method outperforms classic maximum likelihood.…”
Section: Lineage Reconstructionmentioning
confidence: 99%
“…Davidsen and Matsen [308] compared maximum likelihood and maximum parsimony methods for BCR lineage reconstruction. They concluded that an improved and informed maximum parsimony method outperforms classic maximum likelihood.…”
Section: Lineage Reconstructionmentioning
confidence: 99%
“…Furthermore, there exist several methods to construct phylogenetic trees, including distance-based metrics, maximum likelihood (ML), maximum parsimony (MP), and Bayesian inference (Stamatakis, 2006;Gascuel, 2006;Bouckaert et al, 2014). While there exist multiple simulation tools capable of exploring how inference method impacts the resulting phylogenetic trees derived from simulated B cell data (Yermanos et al, 2017;Davidsen and Matsen IV, 2018;Safonova et al, 2015;Weber et al, 2019), the extent of this influence on the evolutionary conclusions on experimental data remains largely unexplored. It remains unknown, for example, the extent of which the phylogenetic inference strategy impacts the biological conclusions pertaining to the evolutionary landscape across various infection cohorts.…”
Section: Introductionmentioning
confidence: 99%
“…Emergence of Rep-seq technologies triggered developments of various clonal tree reconstruction approaches (Barak et al, 2008, Davidsen andMatsen, 2018) such as likelihood-based ImmuniTree (Sok et al, 2013) and IgPhyML (Hoehn et al, 2017) algorithms. Horns et al, 2016 proposed a minimum spanning tree (MST) algorithm for clonal tree reconstruction and applied it to barcoded Rep-seq datasets that were error-corrected using unique molecular identifiers (a similar MST-based BRILIA tool was developed by Lee et al, 2017).…”
Section: Introductionmentioning
confidence: 99%